IMPORT SUBSTITUTION AS THE BASIS OF FOOD SECURITY OF KAZAKHSTAN - G. Zh. Azretbergenova; B. S. Myrzaliyev; M. B. Onbaeva; M. E. Munasipova (Экономика: стратегия и практика)
The article examines the problems of food security as a component of the state’s economic security in the context of the globalization of the world economy. Proved the need for the formation and development of the system of import substitution of food products in Kazakhstan, which is objectively determined and is the most important factor in achieving food security. Only then the rational use of the enormous agricultural potential can remove almost all the issues of reliable provision of domestic food that will allow the country to occupy a worthy place in the global food and food market.